Right To The City: a Scientific Production Review (1995-2018) - Brito, Mozar Jose de; Andrade, Luis Fernando Silva [UNESP] (Univ Estado Rio Janeiro, 2022)
Right to the city is a request for a renewed and transformed urban life according to Henri Lefebvre, French philosopher, and was later discussed by several other authors, like David Harvey, Elden and Purcell. The purpose of this article is to identify and describe the use of the expression, 'right to the city'. Specifically, we aim to understand the publication trends and the use of the expression as cited by most researchers on the research front and on an intellectual basis as were found in our research. For this purpose, used bibliometric and sociometric analysis found in 809 articles on the web of science and analysis of analytical categories, thus, 'socio-spatial formation', 'scalarity', 'abstraction' and 'difference' in texts considered on the research front and intellectual basis which threw more light on this topic. The results indicate a marked increase in the number of articles in the last decade, reflecting social movements with worldwide visibility, such as the Arab Spring, Occupy, Indignados and Jornadas de 2013 and the appropriation of the concept by urban justice activists as a means of analyzing and neoliberal urbanism, as well as the institutionalization of the right to the city. They also indicate the prominence of Brazilian scientific production in periodicals of geography, law and public policies. For the analytical categories, the study shows that Lefebvre's later propositions, which complement the discussion of Right to the City, are less used in the field, as well as authors dealing with socio-spatial formation.
Keywords: Socio-spatial Formation; Collective Rights; Urban Life; Bibliometrics; Scientometrics; Citespace